The numerical solution of partial differential equations with local polynomial regression(LPR) - Çağlar, Hikmet; Çağlar, Nazan; Çağal, Behiç (EUDOXUS PRESS, LLC, 1424 BEAVER TRAIL DRIVE, CORDOVA, TN 38016 USA, 2009)
In this paper, we extended the LPR method to solve the partial differential equations. Numerical experiments are presented to demonstrate the utility and the efficiency of the proposed computational procedure.
Keywords: local polynomial regression (LPR); convection diffusion; heat equation; yerel polinom regresyon (LPR); konveksiyon difüzyon; ısı denklemi